2014
DOI: 10.1142/s0219649214500221
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Vehicle Routing Problem: A Literature Survey

Abstract: Abstract. The purpose of this paper is to develop structural classi¯cation of Stochastic Vehicle Routing Problem (SVRP) by di®erent domains and attributes. This research used a systematic review and meta-analysis on SVRP literatures. This includes browsing relevant researches and publications, screening related articles, identifying domains, attributes and categorising the articles based on the identi¯ed domains and attributes. Thē ndings of the study show clear di®erences on the number of studies under each d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…In this section we hence do not consider dynamic VRPs and rather focus on existing studies that have been carried on static and stochastic VRPs. Specific literature reviews on the SS-VRP may be found in Gendreau et al (1996b), Bertsimas and Simchi-Levi (1996), Cordeau et al (2007), Campbell and Thomas (2008a) and recently in Toth and Vigo (2014), Berhan et al (2014), Kovacs et al (2014) and Gendreau et al (2016). According to Pillac et al (2013), the most studied cases in SS-VRPs are:…”
Section: Related Workmentioning
confidence: 99%
“…In this section we hence do not consider dynamic VRPs and rather focus on existing studies that have been carried on static and stochastic VRPs. Specific literature reviews on the SS-VRP may be found in Gendreau et al (1996b), Bertsimas and Simchi-Levi (1996), Cordeau et al (2007), Campbell and Thomas (2008a) and recently in Toth and Vigo (2014), Berhan et al (2014), Kovacs et al (2014) and Gendreau et al (2016). According to Pillac et al (2013), the most studied cases in SS-VRPs are:…”
Section: Related Workmentioning
confidence: 99%
“…Vehicle routing problem have received increasing attention in recent years. However, in practical situations, the deterministic and single VRP cannot cover real-life contexts, the objectives can be multiple [20] and some components of the VRP are random [25]. In this work, we are interested an important variant of VRP, the so called multiobjective stochastic VRP with two stochastic objectives.…”
Section: Case Study:stochastic Multi-objective Vrpmentioning
confidence: 99%
“…Three recent surveys on dynamic vehicle routing problems were presented by Pillac et al (2013), Bektas et al (2014) and Psaraftis et al (2015). A review of stochastic vehicle routing problems was written by Berhan et al (2014), and nally, a survey of dynamic and stochastic vehicle routing problems was presented by Ritzinger et al (2015).…”
Section: Literature Reviewmentioning
confidence: 99%